2011
DOI: 10.1080/10496475.2011.629776
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Phytochemicals and Antioxidant Properties in Ginger (Zingiber officinaleRoscoe) Rhizome with Different Drying Methods

Abstract: Effects of drying methods on the stability of phytochemicals and antioxidant properties of ginger (Zingiber officinale) were assessed. The rhizomes were collected at 9 and 12 months after planting and sun-dried, freeze-dried, or oven-dried at 40 • , 50 • , 60 • , or 70 • C. Oven drying at 60 • C resulted in significant gains of phenolics (441.85 mg.100g -1 d.w), antioxidant activities (78.45 ± 2.04% and 650.45 ± 50.04 μmol Fe (II).g -1 dry extract) of ginger rhizomes at 9 months after planting. Oven drying at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
2
15
2
Order By: Relevance
“…A shorter drying time is required at higher drying temperatures, resulting in the similar values of TPC in samples dried at diff erent temperatures. This result is inconsistent with that of Chumroenphat et al (2011), who reported that the TPC in ginger rhizome increased with increasing drying temperature.…”
Section: Total Phenolic Contentcontrasting
confidence: 56%
See 3 more Smart Citations
“…A shorter drying time is required at higher drying temperatures, resulting in the similar values of TPC in samples dried at diff erent temperatures. This result is inconsistent with that of Chumroenphat et al (2011), who reported that the TPC in ginger rhizome increased with increasing drying temperature.…”
Section: Total Phenolic Contentcontrasting
confidence: 56%
“…This is probably due to a lower value of TPC in the blanched sample. Chumroenphat et al (2011) found a positive correlation between TPC and DPPH assay of ginger extracts; the samples with higher TPC showed higher antioxidant activity. This indicated that phenolic compounds in ginger contributed to their antioxidant activity.…”
Section: Antioxidant Activitiesmentioning
confidence: 89%
See 2 more Smart Citations
“…While decrease in TPC with the increase in temperature from 40°C to 70°C was published for cocoa bean (10), sweet corn (11), tomatoes (12), carrots (13), gac fruit (14), leaves of Stevia (15) or jaboticaba fruit (16), the increase in TPC with the increase of drying temperature was observed for apple (17), ginger rizome (18), cucumber (19) or quinoa seed (20).…”
Section: Introductionmentioning
confidence: 98%